1992
DOI: 10.1007/bf00260757
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between lipid availability and protein utilization during prolonged fasting

Abstract: Mammals and birds adapt to prolonged fasting by mobilizing fat stores and minimizing protein loss. This strategy ends with an increase in protein utilization associated with behavioural changes promoting food foraging. Using the Zucker rat as a model, we have investigated the effect of severe obesity on this pattern of protein loss during long-term fasting. Two interactions between the initial adiposity and protein utilization were found. First, protein conservation was more effective in obese than in lean rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
114
1
6

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(131 citation statements)
references
References 29 publications
10
114
1
6
Order By: Relevance
“…Regulators of muscle protein turnover include insulin, glucagon, glucocorticoids, thyroid hormones, GH and IGF-1 (Goldberg et al, 1980;Koea et al, 1992). Although low insulin levels may be required for net proteolysis, previous studies have not suggested a role for insulin in regulating net proteolysis during extended fasting (Goodman et al, 1980;Cherel et al, 1992). Similarly, IGF-1 and GH affect protein synthesis and increases in these hormones could reflect a progressive shift in muscle sparing.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Regulators of muscle protein turnover include insulin, glucagon, glucocorticoids, thyroid hormones, GH and IGF-1 (Goldberg et al, 1980;Koea et al, 1992). Although low insulin levels may be required for net proteolysis, previous studies have not suggested a role for insulin in regulating net proteolysis during extended fasting (Goodman et al, 1980;Cherel et al, 1992). Similarly, IGF-1 and GH affect protein synthesis and increases in these hormones could reflect a progressive shift in muscle sparing.…”
Section: Discussionmentioning
confidence: 99%
“…Extended fasting is characterized by mobilization and use of lipid for energy metabolism and reduced mobilization and use of body proteins stores for gluconeogenesis and metabolism (e.g. Cherel et al, 1992). For many species extended fasts are associated with periods of reduced body temperature and activity levels (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 But fat mass is extensive and capable of sustaining life for weeks to months to years in the severely obese in the absence of food intake. 3 This has led to the thrifty gene hypothesis, 4 a concept not accepted by all. 5 The regulation of weight could be the defense of protein, carbohydrate and/or fat.…”
Section: Fat Mass Regulationmentioning
confidence: 99%